2016
DOI: 10.4049/jimmunol.1502038
|View full text |Cite
|
Sign up to set email alerts
|

Spring Viremia of Carp Virus N Protein Suppresses Fish IFNφ1 Production by Targeting the Mitochondrial Antiviral Signaling Protein

Abstract: For a virus to replicate efficiently, it must try and inhibit host IFN expression because IFN is an important host defense at early stages after viral infection. For aquatic viruses, the mechanisms used to escape the hosts IFN system are still unclear. In this study, we show that the N protein of spring viremia of carp virus (SVCV) inhibits zebrafish IFNφ1 production by degrading the mitochondrial antiviral signaling protein (MAVS). First, the upregulation of IFNφ1 promoter activity stimulated by polyinosinic:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 59 publications
2
44
0
1
Order By: Relevance
“…Zebrafish IFNw1 and IFNw3 promoter luciferase reporters and the EPC IFN promoter luciferase reporter could be induced by poly(I:C), whereas zebrafish IFNw2 and IFNw4 promoter luciferase reporters could not be induced by poly(I:C) (36). These inductions are validated in Fig.…”
Section: Zebrafish Foxo3b Inhibits Svcv or Poly(i:c)-induced Ifn Actisupporting
confidence: 58%
See 3 more Smart Citations
“…Zebrafish IFNw1 and IFNw3 promoter luciferase reporters and the EPC IFN promoter luciferase reporter could be induced by poly(I:C), whereas zebrafish IFNw2 and IFNw4 promoter luciferase reporters could not be induced by poly(I:C) (36). These inductions are validated in Fig.…”
Section: Zebrafish Foxo3b Inhibits Svcv or Poly(i:c)-induced Ifn Actisupporting
confidence: 58%
“…It has been reported that similar to that of mammalian species, the fish RLR signaling cascade can activate IFN expression (36). To determine whether zebrafish foxo3b also inhibits IFN expression through its effect on RLR signaling pathway, we examined the activity of ISRE-luc, IFNw1-luc, IFNw3-luc, and EPC-IFN-luc stimulated by overexpression of cascaded factors in the RLR signaling pathway, including the zebrafish N-terminal domain of rig-1 (rig-1-Nter), mavs, tbk1, irf3, or irf7 together with empty Myc vector or Myc-tagged foxo3b.…”
Section: Foxo3b Suppresses Ifn Activation Via Irf3 and Irf7mentioning
confidence: 89%
See 2 more Smart Citations
“…To generate the EGFP-IRF6 expression plasmid, the cDNA fragment encoding IRF6 was cloned into pEGFP-N3 vector (BD Clontech). The plasmids containing IFN41pro-Luc (NM_207640.1), IFN43pro-Luc (NM_001111083.1), and ISRE-Luc in pGL3-Basic luciferase reporter vectors (Promega) were constructed as described previously [28]. All constructs were confirmed by DNA sequencing.…”
Section: Gene Cloning and Plasmid Constructionmentioning
confidence: 99%